Si Imun: Sistem Informasi Imunisasi bagi Puskesmas Berbasis Web - Hidayat Kusuma, Dedy; Andayani, Sri; Nur Shodiq, Moh.; Yuliandoko, Herman; Fuad Al Haris, Muhammad; Arief Wardhany, Vivien; Kumala, Dana (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Indonesia is one of the countries that mandates complete basic immunization for children aged 0–9 months. This immunization is essential to prevent infectious diseases in children. Moreover, the immunization schedule plays a crucial role in the development of a child's immune system. If immunization is administered earlier than scheduled, it may render the vaccination invalid, requiring it to be repeated. Conversely, delayed immunization can lead to a weakened immune response in the child. Therefore, adherence to the immunization schedule is critical to ensure the effectiveness of the immunization process. At present, the dissemination of immunization schedules by the Posyandu (integrated health service post) managed by the Sumberberas Public Health still relies on traditional methods which are often ineffective in reaching all intended recipients. In response to this issue, a web-based immunization scheduling information system is needed to facilitate more efficient and comprehensive dissemination of information. The system is enhanced with an SMS gateway to deliver schedule reminders, enabling timely communication of immunization schedules to parents, even without face-to-face contact. This information system also generates validation reports to support decision-making regarding the necessity of re-immunization, as well as child growth charts to monitor the development of each child over time